Psychological Well-Being During Adolescence: Stability and Association With Romantic Relationships - Gómez-López, Mercedes; Viejo, Carmen; Ortega-Ruiz, Rosario (Frontiers in Psychology, 2019)
The concept of well-being is complex and is in common use not only in the area of health but also in the field of human development. Well-being depends on both the individual and the environment, and during childhood and adolescence, the environmental factor can be decisive. Family, school and peers are widely recognised as significant contexts for successful development, but romantic context is also undoubtedly important. Romantic relationships constitute a new dimension in the adolescent’s social life, but little attention so far has been paid to their importance in well-being. Defined as developmental tasks, they have been associated both positive and negative outcomes, although their impact on well-being has not yet been clarified. This study uses a eudaimonic approach to evaluate four dimensions of psychological well-being: self-acceptance, positive interpersonal relationships, autonomy, and life development, and has a two-fold objective: a) to analyse adolescents’ levels of psychological well-being and their stability over time; and b) to analyse the association between romantic relationships and adolescents’ psychological well-being . Using a longitudinal design, we analysed data from a sample of 747 adolescents from Andalusia (Spain) between 13 and 17 years old (50.5% girls, mean age wave 1 = 14.55, SD = 0.84). The results revealed medium to high levels of psychological well-being, which remained stable throughout the time of the study, and an increase in wave 2 only in positive interpersonal relationships dimension. The Structural Equation Modeling analysis showed romantic relationships as a predictor of psychological well-being, having a positive link with positive interpersonal relationships and with life development, and a negative link with autonomy and self-acceptance. These results are discussed in terms of the need to use approaches focused on the specific characteristics and evolution of well-being during adolescence, as well as on the importance of considering romantic relationships as developmental assets which have the potential to influence the well-being during these years.